The Effect of Risk Profile, Company Size, Profitability, Liquidity, and Leverage on Firm Value in Mining Companies Listed on the Indonesia Stock Exchange (IDX) in 2022–2024 - Nila Wahyu Maya Lestari; Elen Puspitasari (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to examine the effect of risk profile, firm size, profitability, liquidity, and leverage on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research employed a quantitative approach using secondary data obtained from corporate financial statements. The sample was selected through purposive sampling, resulting in 91 observations. Data were analyzed using multiple linear regression with IBM SPSS version 25. Prior to hypothesis testing, classical assumption tests were conducted, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The findings reveal that risk profile has a negative and significant effect on firm value, indicating that higher corporate risk tends to reduce investors’ perceptions of firm value. Leverage has a positive and significant effect on firm value, suggesting that optimal debt utilization can enhance investor confidence and increase firm value. Meanwhile, firm size, profitability, and liquidity do not significantly affect firm value. The simultaneous test results indicate that all independent variables collectively influence firm value. The Adjusted R Square value of 0.116 indicates that the model explains 11.6% of the variation in firm value, while the remaining 88.4% is explained by other factors outside the model. These findings imply that risk management and financing structure play crucial roles in enhancing the value of mining companies.